A Longitudinal, Prospective Study to Evaluate the Effects of Treatment on the Inhibitory Control Function After Transsphenoidal Surgery for Pituitary Adenomas. (October 2021) - Cao, Chenglong; Song, Jian; Lin, Pan; Yan, Deqi; Yao, Shun; Yue, Jianren; Liu, Binbin; Lu, Yuzhao; Xu, Guozheng
Objectives: Injured cognitive abilities have been reported in patients with pituitary adenoma. However, to date, few researchers have directly investigated the electrophysiological study of inhibitory control function of pituitary patients both pre- and postsurgery. Thus, this study aimed to identify the factors affecting the inhibitory control function of pituitary patients. Methods: Thirty presurgery pituitary patients were recruited and 26 patients of them completed the postsurgery follow-up. Thirty healthy people were recruited for control group. Visual Go/Nogo tasks were carried out by the patients and controls to assess the inhibitory control function before surgery and 6 months after the surgery, respectively. The function of inhibitory control was analyzed with the components of N2 and P3. Results: Across 3 groups, Nogo stimuli evoked larger frontal-central N2nogo and P3nogo than Go stimuli did. Furthermore, N2d of presurgery patients (−1.14 μV) and postsurgery patients(−0.61 μV) were significantly decreased compared with that of control group (−3.09 μV), F (2, 83) = 13.92, P < .01, whereas no difference was detected between pre- and postsurgery groups. There was no remarkable difference in the amplitude of P3d among the 3 groups, F (2, 83) = 0.19, P > .05. With regard to the amplitude of P3 for Go condition, The P3 amplitude of healthy group (4.38 μV) was larger than both pre- and postsurgery (1.00 μV and 3.01 μV). With regard to the amplitude of P3 for Nogo condition, The P3 amplitude of healthy group (5.25 μV) was larger than both pre- and postsurgery groups (2.35 μV and 4.18 μV). Conclusions: These results indicated that presurgery patients showed the dysfunction of inhibition, due to the nerve tissue damage or brain structure alteration caused by the presurgery physical pressure from tumor and abnormal hormone levels. Postsurgery patients showed a tendency toward recovery, but there was no obvious improvement in the inhibitory control function after successful treatments.